2011
DOI: 10.2527/jas.2010-3640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing lysine on carcass composition and cutting yields of immunologically castrated male pigs

Abstract: The objective of this experiment was to determine if increasing lysine in the diets of immunologically castrated (IC) male pigs would increase percentage fat free lean and carcass cutting yields when compared with physical castrates. The anti-gonadotropin-releasing factor (GnRF) immunological product (Improvest, Pfizer Animal Health) is used worldwide to immunologically castrate entire male pigs to control boar taint and take advantage of the inherent ability of the entire male to deposit more muscle, less fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
6
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 21 publications
9
61
6
4
Order By: Relevance
“…Efecto de la concentración de lisina y de la adición de ractopamina en las características sensoriales de la carne de cerdo £ Estudios enfocados a incrementar la productividad en función de la cantidad de carne producida, normalmente evalúan el efecto de concentraciones elevadas de proteína y lisina, ya que tienden a optimizar la eficiencia alimenticia. Desafortunadamente, los niveles elevados de lisina y proteína, tienen el efecto inverso en calidad de la carne, ya que tienden a reducir linealmente la GIM y a aumentar la fuerza de corte del lomo (17,42) . Por ejemplo, Apple (43) encontró que en dietas con RAC y una elevada concentración de lisina (2.4 ó 3.1 g lisina/Mcal), se redujo la GIM y aumentó la fuerza de corte.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Efecto de la concentración de lisina y de la adición de ractopamina en las características sensoriales de la carne de cerdo £ Estudios enfocados a incrementar la productividad en función de la cantidad de carne producida, normalmente evalúan el efecto de concentraciones elevadas de proteína y lisina, ya que tienden a optimizar la eficiencia alimenticia. Desafortunadamente, los niveles elevados de lisina y proteína, tienen el efecto inverso en calidad de la carne, ya que tienden a reducir linealmente la GIM y a aumentar la fuerza de corte del lomo (17,42) . Por ejemplo, Apple (43) encontró que en dietas con RAC y una elevada concentración de lisina (2.4 ó 3.1 g lisina/Mcal), se redujo la GIM y aumentó la fuerza de corte.…”
Section: Discussionunclassified
“…Unfortunately, high lysine and protein levels have an inverse effect on meat quality, producing a linear decrease in IMF and an increase in loin shear force (17,42) . For example, diets containing RAC and a high lysine concentration (2.4 or 3.1 g lysine/Mcal) reduced IMF and raised shear force (43) .…”
Section: Resultados Y Discusiónmentioning
confidence: 99%
“…Thus immunocastrates could have a higher anabolic lean growth potential than surgical castrates even though testosterone production is compromised, provided their nutritional needs are met. This potential change in anabolic growth potential and nutritional requirements was investigated by increasing dietary lysine in the diets of immunocastrates, showing that their cutting yields improved and backfat thickness decreased in comparison to surgical castrates (Boler et al, 2011). Responses to varying dietary protein content also differed between immunocastrates and intact males with regards to backfat deposition, also indicating a possible difference in anabolic growth potential and nutritional requirements between immunocastrates and intact boars (Needham & Hoffman, 2015a).…”
Section: Swinementioning
confidence: 99%
“…It has been made evident that dietary lysine is important to optimize the carcass characteristics and yields of finisher pigs when fed with and without RAC (Apple et al, 2004a;Webster et al, 2007). Boler et al (2011) has also shown that immunocastrates (ic) should be fed at a higher lysine level than surgical castrated pigs in order to increase carcass cutting yields and decrease backfat thickness.…”
mentioning
confidence: 99%